Jornal Pessoal: uma metalinguagem jornalística na Amazônia - Amorim, Célia Regina Trindade Chagas (2008)
This work is entitled Jornal Pessoal: a journalistic metalanguage in the Amazon. The object studied is the alternative journal of the sociologist and journalist Lúcio Flávio Pinto. The periodical has been released for 20 years, in Belém, state of Pará. The hypothesis examined is that the journal presents journalistic metalanguage based in the principles of street journalism truth, ethic and liberty as well as of its practice. The generator problem of this investigation arose from the following question: why turning to the study of journalistic metalanguage through an alternative journal if the general press, considered as a journalism paradigm, contains metalinguistic elements? The main objective is to reflect on the importance of alternative media in the process of construction of a journalism effectively committed to society. The theoretical and interpretative basis involved the concept of metalanguage, a second language which analyses the first one, the object language. The theorists studies in the international field like Habermas, John Downing, Carnap, Jakobson, Barthes, Jesús Martín-Barbero and Nelson Traquina, besides Brazilian researchers like Bernardo Kucinski, Ciro Marcondes Filho, Perseu Abramo and Nelson Werneck Sodré were fundamental to explain, in the light of the communication theories, the press language and history, the phases and the proposed objectives. The methodology followed a qualitativedescriptive analysis of the periodical production, mainly the one emphasizing the journalistic language in its 20 years existence. From the 400 editions published, 40 were selected, that is, 10% of each group of 100 samples were extracted, in order to design a profile of the metajournalism of the Jornal Pessoal. This work is also included in the Communication area, a Journalism subfield, more specifically related to alternative media. At present, this expression has been more used in the researchers meetings in Brazil and abroad due to the possibility to shelter several alternative objects. The results achieved are relevant to the Communication field, once they present a new perspective to the alternative media, which must be free of prejudices as to associate those means to a minor, marginal, type of press. They also show the need of studies emphasizing the history of the press aiming at understanding the transformation process through which the journalistic production passed in the capitalism context, and finally, the singularity of this PhD research which was to examine, through the journalistic metalanguage expressed by an alternative journal, the excessive ethic nature deviations in the great Amazon press, mainly in Belém, state of Pará, which compromise the consolidation of a journalism concerned with the citizen